2016
DOI: 10.1186/s13601-016-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive LTP sensitization in food-dependent exercise-induced urticaria/anaphylaxis: a pilot study of a component-resolved and in vitro depletion approach

Abstract: BackgroundChallenge tests for food-dependent exercise-induced anaphylaxis (FDEIA) carry some risk and have a high rate of false negatives. Our aim was to explore the usefulness of an in vitro immunodepletion assay and an allergen microarray test in the identification of IgE-mediated cross-reactive food allergens in patients with suspected FDEIA or food-dependent exercise-induced urticaria and panallergen sensitization.MethodsThree patients with a history of food dependent exercise induced urticaria/anaphylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…These results diverge from other European studies,where hazelnut was the most frequent TN [8,24].In a case-series reported from a single center in our country, in Coimbra, TNs were the main cause of FIA in adults, especially walnut and hazelnut [27].By contrast, in arecent study also conducted in our country, involving preschoolers, cashew and walnut were the commonestTNs [26]. LTPsare a common cause of FIA in the Mediterranean area [9,[28][29][30],and have been pointed out as the main elicitor of FDEIA [28,30,31].Food management in these patients is challenging [30][31][32],due to the presence of these panallergens in a great number of plant foods,like fresh fruits, vegetables, TNs and seeds.In studies conducted in Italy [28] and Spain [32], LTPs are reported as the main cause of FIA in adults, especially peach. In this registry, peach is also of particular relevance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results diverge from other European studies,where hazelnut was the most frequent TN [8,24].In a case-series reported from a single center in our country, in Coimbra, TNs were the main cause of FIA in adults, especially walnut and hazelnut [27].By contrast, in arecent study also conducted in our country, involving preschoolers, cashew and walnut were the commonestTNs [26]. LTPsare a common cause of FIA in the Mediterranean area [9,[28][29][30],and have been pointed out as the main elicitor of FDEIA [28,30,31].Food management in these patients is challenging [30][31][32],due to the presence of these panallergens in a great number of plant foods,like fresh fruits, vegetables, TNs and seeds.In studies conducted in Italy [28] and Spain [32], LTPs are reported as the main cause of FIA in adults, especially peach. In this registry, peach is also of particular relevance.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study carried out in our country [30],including both children and adults, LTPswerethe third cause of FIA, only preceded by shellfishand CM. In the specific approach to FDEIA, avoidance of the implicated foods for at least 4 hours before exerciseis essential [30,31] and sports should be practiced with a partner capable of administering AAI. DIAwas theleadingcause of anaphylaxis in adults, with NSAIDs predominating over antibiotics, as it has been also reported in studies conducted in Spain [11,33].In this study, a low proportion of DIA was noticed in children, asdescribed by others [8,13,34].NSAIDs were the main cause of DIA, as found in other case-series of nonhospitalized patients [33,35,36];however, in several studies,antibiotics are the first cause of DIA [10, 25,34,37,38],and a high risk of penicillin anaphylaxis is estimated in the general population(0.7 to10%) [38].Among NSAIDs, preferential cyclooxygenase-1 inhibitors were the main implicated, especially ASA, ibuprofen, diclofenac andmetamizole, as found in other case-series [8,17,35,36].Anaphylaxisto selective cyclooxygenase-2 inhibitors NSAIDswas rare, reinforcing these as alternative drugs [17,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The ImmunoCAP were then centrifuged at 1700g for 2 min and the depleted serum was collected, pooled and immediately tested [11,12].…”
Section: Plos Onementioning
confidence: 99%
“…Patients with cholinergic urticaria that develop hives after exercising or after any other trigger that elevates core body temperature may be at risk of anaphylaxis (18,19). Exercise may trigger urticaria, which may also be an early manifestation of exercise-induced anaphylaxis.…”
Section: Exercise-induced Urticariamentioning
confidence: 99%
“…These increase intestinal permeability and allow increased antigen uptake, thus causing the disease symptoms. Consequently, hives and anaphylaxis occur shortly after patients exercise (19). Prompt treatment is necessary for patients.…”
Section: Exercise-induced Urticariamentioning
confidence: 99%